Fractional chaos maps with flower pollination algorithm for partial shading mitigation of photovoltaic systems - Yousri D.; Babu T.S.; Allam D.; Ramachandaramurthy V.K.; Beshr E.; Eteiba M.B. (MDPI AG, 2023)
Global optimization; Irradiation; Photovoltaic cells; Solar power generation; Chaos maps; Environmental conditions; Irradiation conditions; Maximum Power Point Tracking; Nonlinear characteristics; Optimization techniques; Partial shading; Solar photovoltaic system; Maximum power point trackers